Influence of inorganic additives on the performance of polysulfone ultrafiltration membrane - Yunos, Muhamad Zaini (Universiti Teknologi Malaysia, 2013)
The influence of zinc oxide and silver (I) oxide in polysulfone ultrafiltration membrane was studied. The membranes were prepared via phase inversion method. The morphology, surface roughness, hydrophillicity and antibacterial properties of membrane were investigated using SEM, AFM and contact angle device consecutively. It was found that membrane with zinc oxide additive has excellent pure water flux as compared to silver (I) oxide. However silver (I) oxide has better humic acid rejection due to the tradeoff effect. SEM-EDX for PSf/silver (I) oxide reveals that the accumulation of silver on top area in cross section of membrane while for zinc oxide seems more concentrated on the bottom. Interestingly, the AFM results support the previous result when PSf/zinc oxide showed better surface roughness on the top of the membrane. Eventhough zinc oxide is known one of antibacterial material, however from qualitative experiment using disc diffusion test (e-coli), there is no inhibition ring for PSf/zinc oxide membrane as compared to membrane with PSf/silver (I) oxide membrane which shows excellence inhibition ring.